Allogrooming, Self-grooming, and Touching Behavior as a Mechanism to Disperse Insecticides Inside Colonies of a Leaf-Cutting Ant - Mota Filho, Tarcísio Marcos Macedo [UNESP]; Camargo, Roberto da Silva [UNESP]; Stefanelli, Luis Eduardo Pontes [UNESP]; Zanuncio, José Cola; dos Santos, Alexandre; de Matos, Carlos Alberto Oliveira [UNESP]; Forti, Luiz Carlos [UNESP] (Springer Nature, 2022)
Toxic baits, containing the active ingredients sulfluramid or fipronil, are the main methods to control leaf-cutting ants of the genera Atta Fabricius, 1805, and Acromyrmex Mayr, 1865 (Hymenoptera: Formicidae). However, the insecticide dispersion among members of the colony during the control needs further studies. We studied whether the behaviors of allogrooming, self-grooming, and contact among individuals spread the insecticides among those of the colony. The insecticides sulfluramid and fipronil (0.1% and 1.0% (w/w)) were applied topically in groups of workers of Atta sexdens (Linnaeus, 1758), and the social interactions among them with or without insecticide were studied. In addition, toxic baits (sulfluramid or fipronil) were provided to colonies and their behavioral acts were observed. At the end of the experiment, colony mortality, number and mass of dead workers, and mass of wet waste were compared between ant nests receiving baits and ants with topical application. In the topical application, behavioral analysis showed higher interaction between ants in the colonies and touch and allogrooming behaviors as the most frequent in those that received the concentrations of sulfluramid. In the baits, the behavior of licking the pellet and allogrooming was more frequent. Colony mortality was faster for those that received topical application, especially with the insecticide fipronil (0.1%). However, the number and mass of dead workers was similar between topical application and toxic baits. In the toxic baits, the licking behavior of the bait pellets and subsequent allogrooming probably dispersed the insecticides. In the topical application, the route of the insecticide occurred by excessive touches among workers, with subsequent allogrooming. Thus, allogrooming, self-grooming, and touching among workers increased the dispersion of insecticides among members of the ant colonies.
Keywords: Atta; Contamination routes; Dispersion insecticides; Social interactions; Trophallaxis